PEMANFAATAN JAMUR ENTOMOPATOGEN BEAUVERIA BASSIANA LOKAL SULAWESI TENGAH UNTUK PENGENDALIAN SPODOPTERA EXIGUA DAN LYRIOMISA CHINENSIS HAMA ENDEMIK PADA BAWANG MERAH DI SULAWESI TENGAH - Rosmini Rosmini; Burhanuddin Nasir (Universitas Tadulako, 2013)
Spodoptera exigua and Lyriomisa chinensis are one of the decstuctive insect and main obstacles in development of onion in Donggala. Pest control by chemicals has been widely reported to give a variety of negative impacts. Other efforts are needed as alternative technology to reduce impact of using synthetic chemical insecticides. One of them is entomopathogenic fungi as bio-insecticide. The objective of this research was to collect Beauveria spp. as enthomopathogen fungy. More specifically, number of Beauveria spp. was collected from several location and host as bio-insecticide formulation matter. There were 12 isolates of Beauveria spp. obtained from various locations in Central Sulawesi. Seven isolates from Lepidoptera while the remaining isolates were two from Homoptera, two from Hemiptera, and one from Coleoptera. Various insect species belong to Lepidoptera order investigated were Spodoptera exigua, Helicoperva armigera, Scirphopaga innotata, Ostrinia furnacalis and Plutella xylostella; belong to Homoptera order were Nilaparvata lugens, and Aphids; belong to Hemiptera order were Leptocoryza acuta; and belong to Coleoptera order was Oryctes rhinoceros. The observation indicated that the color of colony was ranged from yellowish white to white. There was no germination difference among the Beauveria spp. isolates in relationto to their location, host of insects, and insect orders. Differences in virulence showed only in Beauveria isolates from Spodoptera exigua with a high virulence against Spodoptera exigua pest and not for the other insects. Key Words : Beauveria bassiana, Bioinsecticide, Spodoptera exigua Hubn.